Electrostatic flocking of salt-treated microfibers and nanofiber yarns for regenerative engineering. (September 2021) - McCarthy, Alec; Avegnon, Kossi Loic M.; Holubeck, Phil A.; Brown, Demi; Karan, Anik; Sharma, Navatha Shree; John, Johnson V.; Weihs, Shelbie; Ley, Jazmin; Xie, Jingwei
Abstract: Electrostatic flocking is a textile technology that employs a Coulombic driving force to launch short fibers from a charging source towards an adhesive-covered substrate, resulting in a dense array of aligned fibers perpendicular to the substrate. However, electrostatic flocking of insulative polymeric fibers remains a challenge due to their insufficient charge accumulation. We report a facile method to flock electrostatically insulative poly(ε-caprolactone) (PCL) microfibers (MFs) and electrospun PCL nanofiber yarns (NFYs) by incorporating NaCl during pre-flock processing. Both MF and NFY were evaluated for flock functionality, mechanical properties, and biological responses. To demonstrate this platform's diverse applications, standalone flocked NFY and MF scaffolds were synthesized and evaluated as scaffold for cell growth. Employing the same methodology, scaffolds made from poly(glycolide-co-l -lactide) (PGLA) (90:10) MFs were evaluated for their wound healing capacity in a diabetic mouse model. Further, a flock-reinforced polydimethylsiloxane (PDMS) disc was fabricated to create an anisotropic artificial vertebral disc (AVD) replacement potentially used as a treatment for lumbar degenerative disc disease. Overall, a salt-based flocking method is described with MFs and NFYs, with wound healing and AVD repair applications presented. Graphical abstract: This work reports electrostatic flocking of salt-treatment microfibers and nanofiber yarns for applications in wound healing and artificial vertebral disc replacement. Image 1 Highlights: NaCl coatings enable sufficient charge accumulation on electrically insulative polymer fibers during electrostatic flocking. Flocked nanofiber yarns allow further functionalization of flocked scaffolds. Flocked fiber scaffolds sustain cell proliferation. Flocked PGLA (90:10) fiber scaffolds promote modest fiber-density dependent wound healing and angiogenesis. Flock fibers-reinforced elastomeric artificial vertebral discs are mechanically robust.